2011
DOI: 10.1038/jp.2011.174
|View full text |Cite
|
Sign up to set email alerts
|

Viability and neural differentiation of mesenchymal stem cells derived from the umbilical cord following perinatal asphyxia

Abstract: Objective: Hypoxia-ischemia is the leading cause of neurological handicaps in newborns worldwide. Mesenchymal stem cells (MSCs) collected from fresh cord blood of asphyxiated newborns have the potential to regenerate damaged neural tissues. The aim of this study was to examine the capacity for MSCs to differentiate into neural tissue that could subsequently be used for autologous transplantation.Study Design: We collected cord blood samples from full-term newborns with perinatal hypoxemia (n ¼ 27), healthy new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Aly et al34 found that neural differentiation was strongest in cells derived from HIE term neonates, of which 69% exhibited complete and 31% exhibited partial neural differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Aly et al34 found that neural differentiation was strongest in cells derived from HIE term neonates, of which 69% exhibited complete and 31% exhibited partial neural differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Aly et al (2011) demonstrated the transdifferentiation ability of cord bloodderived mesenchymal stem cells towards all three neurological cell types (14). These two findings pave the way for neuro-regenerative therapeutic intervention for management of cerebral palsy.…”
Section: Introductionmentioning
confidence: 90%
“…These two findings pave the way for neuro-regenerative therapeutic intervention for management of cerebral palsy. The finding of Aly et al (2011) introduce autologous stem cells as a convenient therapeutic option.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of hUCBCs may be altered by several factors, such as the gestational age and perinatal asphyxia [100,101]; For example, Aly et al reported that although UCB-MNC count does not differ between healthy-term newborns and term newborns with perinatal asphyxia, neuronal differentiation of hUCB-MSCs is more pronounced in the cells derived from newborns with asphyxia [102]. Apoptosis of neutrophils is impaired in cord blood compared with adult peripheral blood, and the apoptosis is reduced by hypoxia [103].…”
Section: Clinical Trials During Acute Phase Of Brain Injurymentioning
confidence: 98%